2023
DOI: 10.1111/head.14456
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department utilization among patients who receive outpatient specialty care for headache: A retrospective cohort study analysis

Abstract: Objectives: To compare clinical characteristics among outpatient headache clinic patients who do and do not self-report visiting the emergency department for headache.Background: Headache is the fourth most common reason for emergency department visits, compromising 1%-3% of visits. Limited data exist about patients who are seen in an outpatient headache clinic but still opt to frequent the emergency department. Clinical characteristics may differ between patients who self-report emergency department use and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Within the encounters of the four groups examined, significant differences in demographic and baseline factors exist which may suggest explanations for the observed differences in ED utilization rate. The national rural and Kentucky Appalachian groups had higher proportions of encounters with White patients in accordance with anticipated regional demographics; however, prior research has observed a higher age‐adjusted rate of migraine diagnoses in American Indian/Alaskan Native populations, as well as more frequent ED utilization in Black patients with migraine 1,30,31 . In the context of these other observations, it is unlikely that the White race constitutes a unique risk factor for ED utilization.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Within the encounters of the four groups examined, significant differences in demographic and baseline factors exist which may suggest explanations for the observed differences in ED utilization rate. The national rural and Kentucky Appalachian groups had higher proportions of encounters with White patients in accordance with anticipated regional demographics; however, prior research has observed a higher age‐adjusted rate of migraine diagnoses in American Indian/Alaskan Native populations, as well as more frequent ED utilization in Black patients with migraine 1,30,31 . In the context of these other observations, it is unlikely that the White race constitutes a unique risk factor for ED utilization.…”
Section: Discussionmentioning
confidence: 74%
“…The national rural and Kentucky Appalachian groups had higher proportions of encounters with White patients in accordance with anticipated regional demographics; however, prior research has observed a higher age-adjusted rate of migraine diagnoses in American Indian/Alaskan Native populations, as well as more frequent ED utilization in Black patients with migraine. 1,30,31 In the context of these other observations, it is unlikely that the White race constitutes a unique risk factor for ED utilization. Importantly, lower household income was also present in both groups compared to nonrural populations.…”
Section: Discussionmentioning
confidence: 99%